2016
DOI: 10.1111/jmft.12174
|View full text |Cite
|
Sign up to set email alerts
|

Avoid falling for a jerk(ette): Effectiveness of the Premarital Interpersonal Choices and Knowledge Program among Emerging Adults

Abstract: Premarital education may help emerging adults form healthy relationships, but evaluation research is needed, particularly with community samples. We studied emerging adults in the Premarital Interpersonal Choices and Knowledge (PICK) program, using a pre- to post- and a posttest-then-retrospective-pretest design to examine change in perceived relationship skills, partner selection, relational patterns, and relationship behaviors and attitudes. Mixed models analyses showed that scores for the treatment group (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
(59 reference statements)
2
18
0
1
Order By: Relevance
“…Both qualitative and quantitative results were consistent with past research, suggesting that relationship education for singles is associated with a decline in irrational beliefs about relationships (Adler‐Baeder et al, ; Bass, Drake, & Linney, ; Van Epp et al, ), an increase in communication and conflict resolution skills (Antle et al, ), and learning about relationship knowledge and partner selection (Adler‐Baeder et al, ; Bradford et al, ). Three of the four qualitative themes converged (see Figure ), offering broader process‐related information than a focus on program content alone.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Both qualitative and quantitative results were consistent with past research, suggesting that relationship education for singles is associated with a decline in irrational beliefs about relationships (Adler‐Baeder et al, ; Bass, Drake, & Linney, ; Van Epp et al, ), an increase in communication and conflict resolution skills (Antle et al, ), and learning about relationship knowledge and partner selection (Adler‐Baeder et al, ; Bradford et al, ). Three of the four qualitative themes converged (see Figure ), offering broader process‐related information than a focus on program content alone.…”
Section: Discussionsupporting
confidence: 84%
“…For single participants, education is often focused on changes in attitudes and knowledge; thus, response shift may become a methodological issue (i.e., participants realize at posttest the inaccuracy or flaws in their previous ways of thinking). In a recent study of PICK participants, pretest means using the same measures were found to be statistically higher than retrospective pretest means, showing clear evidence of response shift bias (Bradford et al, ). Bias may thus be attenuated by using a retrospective design.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…We make no assumptions about the type of relationship one might choose (and this is highlighted in the workshop), and neither the information nor the skills we provide are geared toward any particular type of romantic or sexual relationship. We also explicitly focus on issues of partner selection, which is covered in some but not all programs (for an example that focuses specifically on partner selection, see Bradford et al, 2016). This is important.…”
Section: Other Relationship Education Programs For Emerging Adultsmentioning
confidence: 99%